ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MAHASISWA DALAM MEMAHAMI MATA KULIAH AUDITING (Studi empiris pada mahasiswa Jurusan Akuntansi di Fakultas Ekonomi UNIMUS dan UNISSULA Semarang) - Ellya Fuadiyah; Fatmasari Sukesti (Universitas Muhammadiyah Semarang, 2013)
This study aims to analyze the factors that students affect on understanding of auditing course. The study based on the motivation's theory that is developed by Maslow and Big Five Personality's theory that is introduced by Goldberg, then it use the variable understanding of auditing course, motivation, communication skills, and personality. The method used is survey research. Analytical instrument to examine the hipotheses and validity of this study uses Structural Equation Model (SEM), it uses AMOS 21.0 program. Whereas, the program that be used in this study for descriptive statistic and reliability analysis uses SPSS 16.0 program, with notice means and standard deviation for statistic descriptive and cronbach alpha value to determine reliability.The results showed that motivati on, communication skills, and personality a studens positive affect on understanding of auditing course. While communication skills no students positive effect on understanding auditing course.Keywords: auditing course, auditing course understanding, motivation, communication skills, personality